SALIA (Liquid Waste Filter) to Reduce Microplastic Pollution from Loundry Waste - Denti Suastikasari; Naura Azahratul Masfufa; Viantika Putri Bakhrudin; Yurika Yasmin Azahra (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Microplastic pollution from laundry waste poses a threat to soil and water. A device called SALIA (Liquid Waste Filter) was created to filter microplastics before the wastewater is discharged into the sewer. Therefore, this study aims to determine the effectiveness of the SALIA device in filtering microplastic particles from laundry wastewater using an experimental method. The device was designed with natural fibers including straw, water hyacinth stems, coconut fiber, luffa, and gravel. Experimental testing was conducted on two device designs: the first with a thickness of 1-2 cm and the second with a thickness of 3-4 cm. The first device, tested with a 1-liter sample, showed an average reduction of 82.35%. Meanwhile, the second device, tested with a 30-liter sample, successfully reduced particles by up to 99%. The results showed that both devices reduced the number of microplastic particles from laundry wastewater. The large thickness of the material makes the filter path long, making microplastics easily trapped. These findings provide hope for efforts to reduce microplastics with simple tools and local materials.